Excitation of torsional modes of proteins via collisional energy transfer: A quantum dynamical approach - Clary, D; Meijer, A (2002)
Quantum theory was applied for the simulation of torsional vibrations in a protein by collision with a solvent molecule. Time-dependent as well as time independent methods were used for solving the scattering problem, and individual excitation of torsional modes was analyzed. A mode-selective effect was found in the computations. Results showed that it was easier to excite backbone torsions than sidechain torsions in the protein.